Murtadha Muthahhari Ecological Vision: Unveiling the Spiritual Foundation of Harmony Between Humans and Nature in Islamic Ecology - Firnando, Hero Gefthi (Faculty of Humanities, Diponegoro University, 2023)
Murtadha Muthahhari, a philosopher and theologian, offers an